Nerodia rhombifer werleri (Hallowell, 1852) (Serpentes: Colubridae), a new record for the ophidiofauna of Puebla, Mexico. - Meza Parral, Yocoyani; Sarmiento Rojas, Amauri; Ramírez Valverde, Tania (Instituto de Ecología, A.C., 2010)
The presence of the Diamondback water snake, Nerodia rhombifer werleri, in the state of Puebla, México is reported here for the first time.